PENDIDIKAN, KESEHATAN DAN PERTUMBUHAN EKONOMI REGIONAL DI INDONESIA: PENDEKATAN MODEL PANEL DINAMIS - Anwar, Aminuddin (Universitas Muhammadiyah Yogyakarta, 2018)
This study analyzes the contribution of human capital ie education and health to regional economic growth in Indonesia. This study uses the regional level of the province as the unit of analysis with the timeframe from 2004 to 2014. Development of economic growth model which is a dynamic model becomes a challenge for estimation of regression model, this study uses generalized method of moment (GMM) as an analytical tool to overcome bias Which occurred on the model of economic growth. This study provides empirical evidence on the role of education and health to regional economic growth in Indonesia. In addition, the estimation results also provide empirical results of conditional convergence with the contribution of human capital that is education and health as a determinant of convergence